Analisis Pengaruh Profitabilitas, Likuiditas, dan Leverage terhadap Financial Distress pada Perusahaan Transportasi yang Terdaftar di BEI Tahun 2018-2020 - Anita Antoniawati; Purwohandoko Purwohandoko (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Financial distress is a condition where management cannot overcome financial problems that cause a successive decline in financial performance before the company is declared bankrupt. This study has something to be achieved, namely analysing the possibility of financial distress in companies with financial ratios as indicators, including profitability ratios, liquidity ratios, and leverage ratios. The sample taken is a transportation company listed on the Indonesia Stock Exchange for 2018-2020. Purposive sampling was used as a sample selection method, and 13 companies were obtained that matched the criteria proposed by the author—data analysis with logistic regression using IBM SPSS version 25. As a result, the profitability represented by ROA does not affect financial distress because when profits decline, there are still other funds from both internal and external sources to cover liabilities. The liquidity represented by the current ratio does not affect financial distress because the companies can fund current debt with total assets. Meanwhile, leverage represented by DAR has a significant effect on financial distress. The solution that transportation companies can do with consecutive losses for 2 years is to be disciplined in paying short-term debts and efficiently use debt capacity to get enormous profits from their obligations to avoid financial difficulties.